ANALISIS KANDUNGAN UNSUR HARA MAKRO PADA MEDIA PERTUMBUHAN JAMBU BOL VARIETAS GONDANGMANIS (Syzygium malaccensei) DI DESA GONDANGMANIS KECAMATAN BANDARKEDUNGMULYO JOMBANG - Nur Laili Sa'adah; Miftachul Chusnah (AGROSAINTIFIKA, 2021)
Gondangmanis guava production has decreased every year, this is due to pests and plant diseases and due to decreased land quality, either due to soil fertility or the absence of cultivation techniques applied to Gondangmanis guava plants. This is caused by several factors, including the lack of supply of agricultural production inputs, the absence of development of guava cultivation technology, the absence of post-harvest technology assembly for guava, and the absence of wider marketing of guava production. soil organic matter, physical properties and macronutrients contained in the land of gondangmanis guava growth. The decline in land productivity will affect the productivity of crop production. Based on this, the author intends to examine how much macro nutrients are available in the Gondangmanis guava growth medium and the soil characteristics of the Gondangmanis guava growing media. The survey and sampling were carried out in the village of Gondangmanis Badarkedung, Mulyo, jombang. Anali This study used a qualitative research using a survey system followed by random sampling of soil at a depth of 0-20 cm. The soil sample is then analyzed in the Integrated Laboratory of the Department of Agriculture. Some of the parameters studied were soil pH determined by a pH meter, N-total was determined by the Kjeldahl method, P-total was determined using the Olsen method, C-organic was determined by the Walkley and black methods. The results of the analysis showed that the chemical content of the soil on the Gondangmanis guava media showed that the soil pH was neutral – alkaline, the C-organic content was very low, the N-total was very low, and the P-total was very high. The soil character of Gondangmanis guava growth media in Gondangmanis village is sandy loam and tends to be sandy.